Trends in intensive care in patients over 90 years of age - Yayan J (Dove Medical Press, 2012)
Josef YayanDepartment of Internal Medicine, Vinzentius Hospital, Landau, GermanyBackground: Average life expectancy has increased over the past century, leading to a larger proportion of elderly in the population. Comorbidity and dependence increases with age, and recent data have shown that the number of elderly patients admitted to intensive care is increasing. This has implications for the availability of health care for these patients, as health care is a finite resource.Objective: This study examines the demographics of patients aged over 90 years who were admitted into the medical intensive care unit, in order to verify the results of previous research.Methods: From 2007 to 2011, a retrospective study was conducted in very elderly patients (over 90 years of age) and elderly patients (between 80 and 89 years of age) admitted into intensive care in Vinzentius Hospital, a medium-size, acute-care, general hospital in Landau, Germany.Results: A total of 8554 intensive care treatments were carried out in the study period. The number of intensive care treatments performed on patients aged over 90 years and those aged 80 to 89 years was 212 (2.48%) and 1715 (20.05%), respectively. No increase in the number of medical intensive care treatments was observed in very elderly patients over this period.Conclusion: Compared to the results of previous studies, an increase in the number of medical treatments in the intensive care units of patients aged over 90 years over the study period could not be found.Keywords: very elderly patients, medical intensive care setting, medical emergency diseases